Euler tours in hypergraphs - Glock, Stefan; Joos, Felix; Kühn, Daniela; Osthus, Deryk (Arxiv, 2018)
We show that a quasirandom $k$-uniform hypergraph $G$ has a tight Euler tour subject to the necessary condition that $k$ divides all vertex degrees. The case when $G$ is complete confirms a conjecture of Chung, Diaconis and Graham from 1989 on the existence of universal cycles for the $k$-subsets of an $n$-set.